KAJIAN KOMPARATIF MINAT BACA SISWA SEKOLAH DASAR DITINJAU DARI PERBEDAAN JENIS KELAMIN PADA MATA PELAJARAN BAHASA INDONESIA - Taqrira, Istiqhara; Sintya, Dita; Febrianty, Syafna; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the reading interest level of male and female students, examine the significant differences, and measure the effect size of gender on reading interest in Indonesian language subjects. A quantitative approach with a comparative design was employed. The population was 30 fifth-grade students (12 males, 18 females) at UPT SPF SD Negeri Minasa Upa. Data were collected using a Likert-scale questionnaire (1-4) and analyzed using descriptive statistics and the Mann-Whitney U test with JASP software. The results showed that female students had a higher mean score (36.61) than male students (34.50). The Mann-Whitney test yielded p = 0.259 (>0.05), indicating no significant difference. The effect size (Rank Biserial Correlation) was 0.250 (moderate effect), suggesting gender contributes only 25% to the difference in reading interest, while 75% is influenced by other factors.